2021
DOI: 10.1016/j.ijmedinf.2021.104613
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' perspective of telehealth during the Covid-19 pandemic

Abstract: Background The COVID-19 pandemic resulted in a rapid and expansive roll out of telehealth applications as a mode of intervention delivery. The effectiveness of this model of care is currently unclear. Objective A cross-sectional observational study evaluating the Irish physiotherapist’s experience of telehealth. Method Irish Physiotherapists completed an online survey, distributed by the Irish Society of Chartered Physiotherapists (ISCP), exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
4
19
0
1
Order By: Relevance
“…A computer or tablet was the most chosen communication medium. This is comparable with previous findings that reported that physiotherapists preferred real-time methods with video technologies over other mediums [ 26 , 36 , 41 , 42 ]. Moreover, the possibilities that the technology provides to the physiotherapy process, rather than the method or technology itself, are important.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A computer or tablet was the most chosen communication medium. This is comparable with previous findings that reported that physiotherapists preferred real-time methods with video technologies over other mediums [ 26 , 36 , 41 , 42 ]. Moreover, the possibilities that the technology provides to the physiotherapy process, rather than the method or technology itself, are important.…”
Section: Discussionsupporting
confidence: 91%
“…The COVID-19 pandemic has led to the rapid adoption of RP by hospitals and clinics. RP has enabled physiotherapists to continue to provide therapy to rehabilitees during the pandemic, prevent further transmission of the virus, and decrease the burden of the health system during this period [ 14 , 36 ]. Rapid implementation of RP was also observed in our study; however, we did not assess the use of RP with rehabilitators due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of Greek PTs used it for follow-ups (68.8%). In a study conducted among PTs working in Ireland, the limited scope of the physical examination (86%) via telehealth is a significant disadvantage [11].…”
Section: Discussionmentioning
confidence: 99%
“…En personas sobrevivientes de COVID-19, la telerrehabilitación tiene el potencial de favorecer el acceso a la rehabilitación en aquellos casos en los cuales no es posible acceder de manera presencial a los servicios. Esta modalidad de atención ofrece una opción rápida y eficaz para responder a las necesidades de rehabilitación especializada que requieren estos pacientes tras el egreso hospitalario.Sin embargo,se han evidenciado algunas limitaciones para la implementacion tales como la dificultad para realizar un examen físico completo, y dificultades que tienen los pacientes, sobretodo de edad avanzada con el manejo de la tecnología (Reynolds, Awan, & Gallagher, 2021). Asi también, puede crear una desigualdad en salud en áreas donde las condiciones socioeconómicas deficientes (por ej.…”
Section: Introductionunclassified